Resolvins: Potent Pain Inhibiting Lipid Mediators via Transient Receptor Potential Regulation - Roh, Jueun; Go, Eun Jin; Park, Jin-Woo; Kim, Yong Ho; Park, Chul-Kyu (Frontiers in Cell and Developmental Biology, 2020)
Chronic pain is a serious condition that occurs in the peripheral nervous system (PNS) and the central nervous system (CNS). It is caused by inflammation or nerve damage that induces the release of inflammatory mediators from immune cells and/or protein kinase activation in neuronal cells. Both nervous systems are closely linked; therefore, inflammation or nerve damage in the PNS can affect the CNS (central sensitization). In this process, nociceptive transient receptor potential (TRP) channel activation and expression are increased. As a result, nociceptive neurons are activated, and pain signals to the brain are amplified and prolonged. In other words, suppressing the onset of pain signals in the PNS can suppress pain signals to the CNS. Resolvins, endogenous lipid mediators generated during the resolution phase of acute inflammation, inhibit nociceptive TRP ion channels and alleviate chronic pain. This paper summarizes the effect of resolvins in chronic pain control and discusses future scientific perspectives. Further study on the effect of resolvins on neuropathic pain will expand the scope of pain research.